Forced displacement in Brazil: Experiences from women treated by Social Assistance - Calderón Uribe, Magaly (2021)
This article sought to understand what displaced women, heads of families assisted by the Social Assistance of Brazil, understand about their displacement process and the State’s actions in regards to it. Through Critical Discourse Analysis it was identified that, although there are several causal attributions to displacement - such as environmental risk and violence - what really runs through the experiences of these women is an exclusionary urbanization, lived throughout the history of these families, which led them to occupy inadequate living spaces such as stream banks and unsuitable land, which ended up being risky and displacing the families in the medium term. Participants understood this situation as a process natural to their social condition, but not as a result of negligence on the part of the State. The results further indicate that the forms of forced displacement are articulated and that environmental displacement serves as State rhetoric to justify displacements related to historical violence and negligence on the part of the State.